1987
DOI: 10.3928/0147-7447-19870401-08
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of PCA Revision Total Knee Replacement Tibial Component: A Preliminary Study Using the Finite Element Method

Abstract: This report documents the results of a finite element method (FEM) "worst-case" failure analysis of a stemmed, porous-coated tibial revision component that was designed with "slots" to aid in removal. A three-dimensional FEM model of a metal-backed tibia! component was subjected to expected peak loads while being restrained at the stem and unsupported under the plateaus. Stresses in the prosthesis plateau adjacent to the stem were found to exceed yield stress in many areas, and to exceed the expected endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…There are fewer than 100 case reports in the literature of TKA tibial baseplate fractures 10 . Critical factors implicated in the failures include prosthesis design, implant positioning and fixation, tibial bone stock, obesity, and high activity level 8,[10][11][12][13][14][15][16][17][22][23][24][25] . Chatterji et al 10 , Abernathy et al 13 , and Flivik et al 16 all indicated that manufacturing errors and deficiency in implant design are also relevant factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer than 100 case reports in the literature of TKA tibial baseplate fractures 10 . Critical factors implicated in the failures include prosthesis design, implant positioning and fixation, tibial bone stock, obesity, and high activity level 8,[10][11][12][13][14][15][16][17][22][23][24][25] . Chatterji et al 10 , Abernathy et al 13 , and Flivik et al 16 all indicated that manufacturing errors and deficiency in implant design are also relevant factors.…”
Section: Discussionmentioning
confidence: 99%